Increased frecuency of the homozygous DD angiotensin converting enzyme genotype in Spanish top level gymnasts - Boraita, A.; Heras, E.; de la Torre, A.; Canda, A.; Rabadan, M.; Diaz, E.; Anton, P.; Garcia, M.; de la Rosa, A.; Lopez, M.; Hernandez, M. (Archivos de medicina del deporte, 2008)
Angiotensin-converting enzyme (ACE) genotype has been reported to be associated with physical performance. While an excess of D allele has been observed in anaerobic disciplines, I allele has been associated with endurance athletes in different studies. Materials and methods: The distribution of ACE genotypes has been investigated in 315 elite athletes (207 men and 108 women) of more than 30 different disciplines. Out of them 12 athletes (9 men and 3 women) practising artistic gymnastic have been selected. The election was based on the high static and low dynamic demands of this discipline, group IIIA of Mitchell`s Classification. The ACE genotype, insertion (I) o deletion (D) alleles, was ascertained by polymerase chain reaction using two pairs of primers. The ACE genotype was compared with the rest of our population of elite athletes. Results: The ACE DD homozygote genotype was observed in 8 gymnasts (67%), 5 men and 3 women, ACE II homozygote was present in 2 cases (17%) and ACE ID heterozygote in other 2 cases (17%). Genotype frequency differs significantly (Chi2 =8,055, p=0,02) from the rest of our population of elite athletes (DD 31,3%, DI 57%, II 11,5% ). Conclusions: The ACE DD genotype is more prevalent among Spanish top level gymnasts than among others Spanish elite athletes, suggesting a positive association between the allele D and performance in high static component disciplines. Nevertheless, this study concerned a population of limited size, so more studies are necessary to confirm the results and to explain the reason of the prevalence of DD ACE genotype in this discipline.